A Cladocora caespitosa bank (National Park Mljet, Adriatic Sea) under climate and anthropogenic impacts: a 20-year survey - KRUŽIĆ, PETAR; GUIĆ, RITA; LIPEJ, LOVRENC; MAVRIČ, BORUT; GRAČAN, ROMANA; ANKON, PAVEL (Mediterranean Marine Science, 2025)
The Mediterranean endemic stony coral Cladocora caespitosa (Linnaeus, 1767) is the only reef-building and obligate zooxanthellate coral in the Mediterranean Sea. This endangered species is threatened by climate and anthropogenic impacts affecting the coastal zone of the Mediterranean Sea. Growth rates and colony state were monitored over 20 years on a C. caespitosa bank in the Marine Protected Area of Veliko Jezero in the Adriatic Sea (Mljet National Park, Croatia). The growth rate of corallites (from 2.02 mm to 5.32 mm annually) was similar to relevant studies in different areas of the Mediterranean Sea and showed a positive correlation with the average annual sea temperature. The coral colonies formed a highly aggregated bank and beds on rocky and sandy bottoms, from 6 to 18 m depth, within a semi-enclosed bay with high water exchange caused by tides. The marine area has experienced abnormally warm summers during the last two decades, with sea temperatures reaching up to 30°C driving population damage to the coral bank. Mortality events of C. caespitosa colonies caused by polyp bleaching and tissue necrosis, showed a positive correlation with high sea temperature anomalies during summer and autumn resulting in complete or partial mortality of the colonies. The excessive growth of macroalgal species on coral colonies seems to be a direct consequence of sewage discharges from nearby villages. The present climate-warming trend together with urbanization has severely and negatively affected the C. caespitosa coral bank in the Mljet National Park causing concerns for future viability.